The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1128/aem.65.2.802-806.1999
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Novel Propachlor Degradation Pathways in Two Species of Soil Bacteria

Abstract: Propachlor (2-chloro-N-isopropylacetanilide) is an acetamide herbicide used in preemergence. In this study, we isolated and characterized a soil bacterium, Acinetobacter strain BEM2, that was able to utilize this herbicide as the sole and limiting carbon source. Identification of the intermediates of propachlor degradation by this strain and characterization of new metabolites in the degradation of propachlor by a previously reported strain ofPseudomonas (PEM1) support two different propachlor degradation path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 17 publications
0
5
2
Order By: Relevance
“…Direct hydrolysis of the tertiary amide in chain A of DAMI is contrary to the results of Helbling et al, who observed an N-dealkylation as the initial reaction in the transformation pathway of tertiary amides under aerobic conditions. In contrast, in two pure culture studies, the tertiary amides of DEET ( N , N -diethyl m -toluamide) and propachlor were also found to be transformed by direct hydrolysis. , No N-dealkylated intermediate TP of DAMI was detected in the batch experiments in this study. However, it cannot be completely excluded that N-dealkylation was the first step in the transformation of the tertiary amide and that subsequent hydrolysis of the resulting secondary amide was considerably faster than the initial N-dealkylation.…”
Section: Resultscontrasting
confidence: 74%
“…Direct hydrolysis of the tertiary amide in chain A of DAMI is contrary to the results of Helbling et al, who observed an N-dealkylation as the initial reaction in the transformation pathway of tertiary amides under aerobic conditions. In contrast, in two pure culture studies, the tertiary amides of DEET ( N , N -diethyl m -toluamide) and propachlor were also found to be transformed by direct hydrolysis. , No N-dealkylated intermediate TP of DAMI was detected in the batch experiments in this study. However, it cannot be completely excluded that N-dealkylation was the first step in the transformation of the tertiary amide and that subsequent hydrolysis of the resulting secondary amide was considerably faster than the initial N-dealkylation.…”
Section: Resultscontrasting
confidence: 74%
“…Because of this, the apparent solubility of PAH is enhanced up to 20‐fold, which is followed by significant increase in biodegradation rate of PAH. It is reported that pure AlnA can also effectively emulsify wide range of other hydrophobic compounds, such as long chain alkanes, aromatics, paraffin, and crude oil .…”
Section: Applications Of Biosurfactants Produced By Acinetobacter Sppmentioning
confidence: 99%
“…Many pharmaceuticals and other xenobiotics whose fate is through WWTPs contain amide groups (see ref for a review of xenobiotics that have been identified in WWTPs). Data in the literature further suggest that amides may either be hydrolyzed or N-dealkylated during biotransformation, but the structural features that may promote or inhibit either biotransformation reaction remain unknown. Accordingly, the UM-PPS contains transformation rules for hydrolysis and N-dealkylation which are both triggered by secondary and tertiary amide substructures.…”
Section: Introductionmentioning
confidence: 99%